Experimental investigations of dynamic compressive properties of roller compacted concrete (RCC). (20th April 2018) - Wang, Chao; Chen, Wensu; Hao, Hong; Zhang, Sherong; Song, Ran; Wang, Xiaohua
Highlights: Dynamic stress–strain curves and failure modes of RCC specimens are obtained. Empirical relations of DIF of compressive strength for RCC are proposed. Influences of aggregate size and lateral inertia confinement on RCC are studied. The effect of bedding surface on the dynamic strength of RCC is examined. Abstract: Roller compacted concrete (RCC) has been widely used in large scale constructions such as hydraulic structures and pavement. Because of the construction process, it has some unique material properties as compared to the ready-mix concrete. Structures made of RCC might be subjected to dynamic loads during its service life. Understanding the dynamic material properties of RCC is essential for better analysis and design of RCC structures. The study on dynamic compressive mechanical properties of RCC is very limited in literature. In this study, dynamic compressive properties of RCC under the strain rate up to 80/s are investigated by using Split Hopkinson Pressure Bar (SHPB). In addition, to investigate the size effects on dynamic impact tests, three sizes of cylindrical RCC specimens with the diameters of 50 mm, 75 mm and 100 mm are prepared and tested. The failure processes and the failure modes of RCC specimens with different dimensions under different strain rates, as well as the stress–strain curves under different strain rates and the energy absorption capacities of the tested specimens are compared. The influences of the specimen size, aggregates grading, and the existence of bedding surface in RCC on its dynamic properties are investigated. Based on the testing results, empirical formulae of DIF (dynamic increase factor) for the RCC compressive strength are proposed to predict the enhancement of material strength at different strain rates.